Gênero e relações de poder no Pentecostalismo: estudo comparativo entre a Igreja de Cristo no Brasil e a Comunidade Evangélica Sara Nossa Terra - Fonseca, Jean-claude Rodrigues da (2009)
Based on the empirical comparative study between two churches from Pentecostal guidance - both located in Parnamirim/RN - and supported on a dialogic interaction between my interlocutors and theoretical references, I proposed me to reflect about how this protestant segment represents and articulates questions such as gender and power relationships, and the daily impact of that in their followers life. In other words, this dissertation aims to understand the reason of the asymmetry attributed to male and female, especially in what concerns the distribution of ecclesiastic works and the authority given to male, as well as the implication of this reality in the reconfiguration of morality and religious praxis in daily life of individuals and involved groups. From this perspective, this work was divided in three chapters, in which I investigate the tension/relationship between faith and secularism, for from this question on concessions and/or prohibitions related to the limits and involvement of the followers with the world and with the very Pentecostal ethos arise. I also analyze here aspects concerning to both ecclesiastic hierarchy and power, with the objective of elucidating how it occurs, what kind of criteria and implications they consider as well as about the nature of the religious labor division between men and women and, finally, I try to understand how the conversion/adhesion of members is reflected in the redefinitions of gender and its relationship between the ecclesiastical and domestic spaces. The diligence and energy spent in this work is in the hope that its fruits can corroborate in the expansion of anthropological knowledge which, in this particular case, involves the Brazilian Pentecostal phenomenon